Faktor-Faktor Penentu Kebijakan Dividen dengan Intervening Profitabilitas - Nurani Puspa Ningrum; Heni Risnawati (Universitas Dian Nuswantoro, 2024)
The dividend payout ratio is the ratio of the total dividends paid to shareholders to the company's net profit. This study aims to test and analyze the relationship of liquidity, debt to total assets (DAR), company size, company growth, and managerial ownership of dividend policy which is calculated using the dividend payout ratio, with the addition of the intervening variable profitability. The sample in this study was taken using a purposive sampling technique from 2018-2022 with a total sample of 120. Sobel analysis was used to analyze the data and the regression used multiple linear regression. The results of this study explain the variables that influence the dividend payout ratio, namely liquidity, company growth, company size, and managerial ownership, while the variables that do not have an effect on dividends are leverage and managerial ownership. The intervening profit variable is known to only be able to intervene in the relationship between liquidity, company growth, and company size to the DPR.